(untitled) (Revista Nacional de Odontología, 2023)
Various studies agree that human teeth are morphologically and histologically similar to those of some mammals. In particular, bovine incisor teeth present some special characteristics similar to those of humans. There is little literature describing the microscopic structure of bovine teeth, this being a key link for the complete histological description of such dental piece, for its potential use as a substitute for the human one. The objective of this manuscript is to identify the histological characteristics of human and bovine dental pieces for their use in research and teaching in dentistry.